Chinese Folk Children’s Song in Preschool Education - Yaqin , Liao; Bunratnang, Ketkaew (Journal of Roi Kaensarn Academi, 2024)
Among the many courses in the preschool education major of colleges and universities, the children’s song singing course is an important professional basic course and one of the core courses of the preschool education major. Whether the setting of this course is scientific or not directly affects the quality of talent training in the preschool education major of colleges and universities. As a college teacher rooted in the grassroots, the author has been engaged in teaching basic piano and children’s song playing and singing in preschool education for a long time. He has accumulated certain theoretical and practical experience in teaching practice, and has read a number of theoretical books on the teaching of children’s works, which has deepened the theoretical understanding and practical application of the teaching work he is engaged in.